SOUTH KOREA’S PUBLIC DIPLOMACY STRATEGY THROUGH THE NEW SOUTHERN POLICY TOWARDS THE SPREAD OF THE KOREAN WAVE IN 2017-2021 - Devita Nadya (Mediasi: Journal of International Relations, 2022)
South Korea is a country that active to conducting public diplomacy. Incarrying out its public diplomacy, the South Korean government uses the KoreanWave as an icon in its diplomacy with other countries. With the Korean Wave, SouthKorea received full attention globally, many international people were interested andwanted to know more about South Korean culture. The Korean Wave are verypopular all over the world starting from its kpop music, dramas, films, food, beautyproducts, language and so on. In 2017, South Korea issued the New Southern Policyduring the reign of Moon Jae In, deciding to establish cooperation with countries inASEAN and India. This policy focuses on the three 3Ps, namely People, Prosperityand Peace. In these 3 cases, the South Korean government sees that this policy hasbeen quite successful in helping to build the country's image and increasing theinterest of the international community to visit and cooperate with South Koreabecause it will be mutually beneficial.Keywords: Korean Wave, New Southern Policy, South Korea, ASEAN